Strategi Badan Kesatuan Bangsa dan Politik Kota Serang sebagai Fasilitator dalam Pembinaan Pendidikan Politik - Purna, Tebi Hariyadi; Bahrudin, Febrian Alwan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the strategy of the National Unity and Politics Agency (Kesbangpol) of Serang City in facilitating the development of political education. This study uses a descriptive method with a qualitative approach to understand social phenomena in depth. According to the context, this method describes phenomena in detail in words and language. The results of this study indicate that Kesbangpol of Serang City plays a role as a facilitator in facilitating the development of political education through various strategies such as socialization, training, and cooperation with the KPU of Serang City, Bawaslu of Serang City and political parties. This study concludes that the strategy implemented by Kesbangpol of Serang City in facilitating the development of political education is an effort to build good political awareness and understanding for the community and increase the political participation of the community in the democratic process. Keywords: Strategy, Facilitator, Political Education